Determination of Lanthanum in Human Blood Serum Using the Zero and First Derivative Spectrophotometry in Micellar Media - Chamsaz, Mahmoud; Rounaghi, Gholamhossein; Hossein Arbab-Zavar, Mohammad; Reza Sovizi, Mohammad (Asian Journal of Chemistry, 2016)
A simple and sensitive method for the determination of lanthanum by zero and first derivative spectrophotometry is described. Lanthanum reacts with xylenol orange in ammonia-ammonium chloride buffer (pH = 8) and cetylpyridiminium chloride. Beer’s law is obeyed 1.44–2.0 × 102 ng mL–1 of lanthanum. The corresponding value of Sandell’s sensitivity is 6.90 × 10–4 μg cm–2. The relative standard deviation evaluated from 10 independent determinations of lanthanum is 1.09. The detection limit based on 3Sb is 4.32 × 10–3 μg mL–1 of lanthanum. The above method was used for determination of lanthanum in synthetic and human blood serum samples.